PENGARUH KEPEMIMPINAN DAN MANAJEMEN BUMDES TERHADAP KEBERHASILAN USAHA BUMDES SYARI'AH USAHA BERSAMA DESA MAHATO SAKTI - Rio Taufik (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
Village Owned Enterprises are economic institutions formed by villages in the context of realizing village economic independence and the welfare of village communities. An organization needs a leader so that organizational goals can be achieved. In addition, they are required to be able to lead BUMDes, from a management or management aspect they must consistently provide social services and also economic businesses that can serve the interests of the village. The objective of this study was to determine the influence of BUMDes leadership and management on the success of the BUMDes Syari'ah Joint Venture of Mahato Sakti Village. The research approach that researchers use is a quantitative approach. The research instruments used were observation and questionnaires. The number of samples of this research as the object of research is 200 respondents. Data analysis technique using IBM SPSS 23 software using multiple linear regression with a significance level of 5%. The results of the study show that Multiple linear regression test on leadership variables, BUMDes management variables, and Y variable BUMDes business success yields a number of 0.027 meaning that Ha is accepted and Ho is rejected, namely that there is a simultaneous significant relationship between BUMDes leadership and management on business success BUMDes Syari'ah Joint Village Business Mahato Sakti. And the contribution of BUMDes leadership and management simultaneously to business success is 8.24%.